1994
DOI: 10.1128/aac.38.2.200
|View full text |Cite
|
Sign up to set email alerts
|

In vitro extracellular and intracellular activities of clavulanic acid and those of piperacillin and ceftriaxone alone and in combination with tazobactam against clinical isolates of Legionella species

Abstract: The activities of ceftriaxone, piperacillin, tazobactam, clavulanic acid, and combinations of ceftriaxone or piperacillin with tazobactam against 22 clinical Legionella isolates were measured by broth microdilution and macrodilution methods and in macrophages. The broth microdilution MICs that inhibited 90%o of strains tested were 2 and 1 ,ug/ml for ceftriaxone and tazobactam, respectively. Broth macrodilution MICs were 8 and 1 ,ug/ml, respectively, for the two LegioneUla pneumophila strains tested with pipera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
1

Year Published

1995
1995
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 36 publications
0
3
1
Order By: Relevance
“…The quantitative MIC was 0.016 g/ml. Our results showed a lower MIC than previous reports by Edelstein et al and Collins et al, which showed MICs between 0.12 and 1 g/ml and between 0.03 and 2 g/ml, respectively, reinforcing the effectiveness of these antibiotics against extracellular forms (4,5).…”
contrasting
confidence: 56%
“…The quantitative MIC was 0.016 g/ml. Our results showed a lower MIC than previous reports by Edelstein et al and Collins et al, which showed MICs between 0.12 and 1 g/ml and between 0.03 and 2 g/ml, respectively, reinforcing the effectiveness of these antibiotics against extracellular forms (4,5).…”
contrasting
confidence: 56%
“…There was only one paper, Jia et al [ 53 ], which used the Broth Microdilution method with the ECOFF interpretation criteria [ 54 ]. Classifying the results according to year or a period of years, it was observed that a significant number of papers from the 1980s and 1990s (18/37; 48.6%) used the Broth Microdilution method according to previously published protocols, such as Edelstein et al [ 55 , 56 , 57 , 58 ], Hoogkamp-Korstanje [ 59 ] and Jones et al [ 60 ] ( Table S1 raw data; Figure 2 and Figure 3 ). Looking at the studies published in the time period 2000–2019, it is interesting to note that 17/57 articles used the Broth Microdilution method, as recommended by the CLSI, but then applied methods cited by older publications instead of the CLSI-recommended method for the interpretation of the results.…”
Section: Resultsmentioning
confidence: 99%
“…In general, conclusions that an antibiotic is bactericidal against intracellular L. pneumophila have been based on the absence of regrowth or very slow regrowth of the bacterium after drug removal from tissue culture wells of infected phagocytes and continued incubation (20,21,28,43). Although such studies demonstrate the ability of the antibiotic to penetrate and concentrate within various types of phagocytic cells, i.e., macrophage-like cells (e.g., U937 cells) or professional phagocytic cells, they do not give any indication of the level of resistance of the intracellular bacterium.…”
Section: Discussionmentioning
confidence: 99%